Ferroptosis caused by cysteine insufficiency and oxidative insult. (1st December 2020) - Fujii, Junichi; Homma, Takujiro; Kobayashi, Sho
Abstract: Free iron has long been assumed to be a deteriorating factor in an oxidative insult and was recently found to be directly associated with ferroptosis, a specific type of cell death. The free iron-involved production of lipid peroxides activates the fatal pathway, resulting in nonapoptotic, programed cell death. Lipid peroxides appear to destroy membrane integrity, leading to cell rupture. Glutathione (GSH) is a major redox molecule that functions to protect against ferroptosis by its ability to donate an electron to glutathione peroxidase 4 (GPX4), the sole enzyme that reduces phospholipid hydroperoxides. The availability of free cysteine (Cys) determines the levels of GSH synthesis, and, hence, its deprivation causes ferroptosis. Free iron is provided via ferritinophagy, the chaperone-mediated autophagic degradation of ferritin, but GPX4 also undergoes degradation via chaperone-mediated autophagy. Activated Nrf2 and ATF4 induce the expression of the cystine transporter xCT to cope with ferroptosis. To the contrary, the excessive activation of p53 induces ferroptosis by suppressing the expression of xCT in genetic and nongenetic manners. It therefore appears that xCT functions as the gatekeeper for determining cellular survival by regulating the availability of Cys in the cell. The issue of the extent of involvement of ferroptosis in an in vivo situation largely remains ambiguous. Establishing tools for specifying ferroptotic cells in situ would facilitate our understanding of its roles in pathogenesis.